Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 21505 species occurrences available in GBIF matching the query: { "and" : [ "Country is Spain", { "or" : [ "TaxonKey is Aconitum burnatii G·yer, 1909", "TaxonKey is Aconitum variegatum subsp. pyrenaicum Vivant & Delay", "TaxonKey is Aquilegia pyrenaica subsp. guarensis (Losa) Rivas Mart.", "TaxonKey is Thalictrum macrocarpum Gren.", "TaxonKey is Thalictrum flavum Thunb., 1784", "TaxonKey is Ruppia maritima L.", "TaxonKey is Saxifraga losae subsp. suaveolens (Luizet & Soulié) Fern.Areces, T.E.Díaz & Pérez Carro", "TaxonKey is Melampyrum nemorosum L.", "TaxonKey is Tamarix boveana Bunge", "TaxonKey is Apium repens Rech.f.", "TaxonKey is Juniperus thurifera L.", "TaxonKey is Ilex aquifolium L.", "TaxonKey is Echium boissieri Steud.", "TaxonKey is Onosma tricerosperma subsp. alpicola (Vayr.) O.Bolòs & Vigo", "TaxonKey is Minuartia cerastiifolia (Ramond ex DC.) Graebn.", "TaxonKey is Petrocoptis crassifolia Rouy", "TaxonKey is Silene borderi Jord.", "TaxonKey is Centaurea emigrantis Bubani", "TaxonKey is Leontopodium alpinum Cass.", "TaxonKey is Scorzonera parviflora Jacq.", "TaxonKey is Boleum asperum (Pers.) Desv.", "TaxonKey is Brassica repanda (Willd.) DC.", "TaxonKey is Cochlearia aragonensis subsp. aragonensis", "TaxonKey is Subularia aquatica L.", "TaxonKey is Carex ferruginea Scop." ] } ] } The dataset includes 21505 records from 89 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0011817-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences